The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1365-2559.2005.02255.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of acyl‐CoA synthetase 5 in human endometrium and in endometrioid adenocarcinomas

Abstract: The abundance of ACS5 in the endometrial epithelium throughout the menstrual cycle provides support for its role in the regulation of tissue homeostasis. With regard to its value for histopathological diagnosis, immunohistochemical characterization of endometrioid adenocarcinomas shows that a decrease in ACS5 expression correlates with tumour dedifferentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In addition, they failed to employ in vitro and in vivo experiments to further explore the role of ACS5 in the progression of CRC. Similar to our study, Gassler et al showed that the higher the expression level of ACS5 in endometrial carcinoma, the higher the degree of tumor differentiation [ 22 ]; Gaisa et al reported that the expression level of ACS5 in normal urothelial tissue was significantly higher than that in tumor tissue and reported a gradual loss of ACS5 expression with decreasing cellular differentiation in urothelial cancers [ 23 ]. These two studies suggested that ACS5 was a tumor suppressor, which was contrary to our findings in colorectal cancer, that may be related to the type of tumor.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, they failed to employ in vitro and in vivo experiments to further explore the role of ACS5 in the progression of CRC. Similar to our study, Gassler et al showed that the higher the expression level of ACS5 in endometrial carcinoma, the higher the degree of tumor differentiation [ 22 ]; Gaisa et al reported that the expression level of ACS5 in normal urothelial tissue was significantly higher than that in tumor tissue and reported a gradual loss of ACS5 expression with decreasing cellular differentiation in urothelial cancers [ 23 ]. These two studies suggested that ACS5 was a tumor suppressor, which was contrary to our findings in colorectal cancer, that may be related to the type of tumor.…”
Section: Discussionsupporting
confidence: 89%
“…Within the context of tumorogenesis, few reports have been published on ACS5. In adenoma and adenocarcinoma of the small intestine ACS5 expression is decreased [54] while it is up-regulated in gliomas [55], in well-differentiated endometrioid adenocarcinomas [56] and in certain colorectal adenocarcinomas [57]. The RT-qPCR data in our panel of tumors revealed an increase in the expression of ACS5 (p = 0.001), eventhough it has not been confirmed by IHC.…”
Section: Discussionmentioning
confidence: 80%
“…ACSL5 expression was variably associated with malignancy, being increased in many colorectal tumors, but decreased in some intestinal tumors including adenocarcinomas (28,29). ACSL5 expression was also increased in well-differentiated, but not poorly-differentiated, endometrial adenocarcinomas (30). ACSL5 mRNA levels were high in primary human gliomas and A172 glioma cells but, in contrast to our findings with ACSVL3, were not detectable in either U87 or U373 glioma cells (31).…”
Section: Discussionmentioning
confidence: 99%